Representing Climate Change through the Lens of Environmental Security: Thirty Years of the Department of Defense Defining a Threat Multiplier and Military Resilience - Michael STRICOF (E-REA)
One of the key ways in which environmental emergency is recognized in the United States is as a military issue through the lens of environmental security. This article proposes an expanded understanding of this concept by taking a historical look at the evolving role of the Department of Defense in defining environmental security from the late 1980s, when the term first gained traction, through the Donald Trump administration. This approach highlights consistent themes in the Pentagon’s environmental mitigation and adaptation plans, notably through its definition of climate change as a threat multiplier and the need to increase the military’s resilience to changing weather conditions. By tracing the Department of Defense’s response to environmental risks over more than three decades, a consistently refined narrative emerges which allows us to understand defense climate priorities, regardless of varying political leadership.